Simulation and experimental study on drag reduction and anti-adhesion of subsoiler with bionic surface - Niu, Jiping; Luo, Tongyun; Xie, Jiaqing; Cai, Haoxuan; Zhou, Zhikang; Chen, Jun; Zhang, Shuo (International Journal of Agricultural and Biological Engineering, 2022)
A new subsoiler with placoid scale microstructure bionic surface was proposed which mimicked shark skin to reduce tillage resistance and soil adhesion during subsoiling cultivation. The contour curves of placoid scale microstructure on shark skin were fitted, and two kinds of bionic subsoiler with continuous and discontinuous microstructures were designed and fabricated, respectively. The effects of different bionic surfaces on tillage resistance were investigated by finite element simulation and experiment. The results indicated that the bionic subsoiler with discontinuous microstructure reduced the horizontal and vertical force by 21.3% and 24.8%, respectively. The subsoiler with discontinuous microstructure surface can prevent the adhesion between the soil and subsoiler surface more efficiently.Keywords: drag reduction, anti-adhesion, subsoiler, bionic surface, placoid scale microstructure, Finite element simulationDOI: 10.25165/j.ijabe.20221504.6531Citation: Niu J P, Luo T Y, Xie J Q, Cai H X, Zhou Z K, Chen J, et al. Simulation and experimental study on drag reduction and anti-adhesion of subsoiler with bionic surface. Int J Agric & Biol Eng, 2022; 15(4): 57–64.